Increased BMP-Smad signaling does not affect net bone mass in long bones - Omi, Maiko; Koneru, Tejaswi; Lyu, Yishan; Haraguchi, Ai; Kamiya, Nobuhiro; Mishina, Yuji (Frontiers in Physiology, 2023)
Bone morphogenetic proteins (BMPs) have been used for orthopedic and dental application due to their osteoinductive properties; however, substantial numbers of adverse reactions such as heterotopic bone formation, increased bone resorption and greater cancer risk have been reported. Since BMP signaling exerts pleiotropic effects on various tissues, it is crucial to understand tissue-specific and context-dependent functions of BMPs. We previously reported that loss-of-function of BMP receptor type IA (BMPR1A) in osteoblasts leads to more bone mass in mice partly due to inhibition of bone resorption, indicating that BMP signaling in osteoblasts promotes osteoclast function. On the other hand, hemizygous constitutively active (ca) mutations for BMPR1A (caBmpr1awt/+) in osteoblasts result in higher BMP signaling activity and no overt skeletal changes in adult mice. Here, we further bred mice for heterozygous null for Bmpr1a (Bmpr1a+/-) and homozygous mutations of caBmpr1a (caBmpr1a+/+) crossed with Osterix-Cre transgenic mice to understand how differences in the levels of BMP signaling activity specifically in osteoblasts contribute to bone phenotype. We found that Bmpr1a+/-, caBmpr1awt/+ and caBmpr1a+/+ mice at 3 months of age showed no overt bone phenotypes in tibiae compared to controls by micro-CT and histological analysis although BMP-Smad signaling is increased in both caBmpr1awt/+ and caBmpr1a+/+ tibiae and decreased in the Bmpr1a+/- mice compared to controls. Gene expression analysis demonstrated that slightly higher levels of bone formation markers and resorption markers along with levels of BMP-Smad signaling, however, there was no significant changes in TRAP positive cells in tibiae. These findings suggest that changes in BMP signaling activity within differentiating osteoblasts does not affect net bone mass in the adult stage, providing insights into the concerns in the clinical setting such as high-dose and unexpected side effects of BMP application.